2020
DOI: 10.1101/2020.11.07.367649
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

In vitro: Natural Compounds (Thymol, Carvacrol, Hesperidine, And Thymoquinone) Against Sars-Cov2 Strain Isolated From Egyptian Patients

Abstract: The current pandemic of the coronavirus disease-2019 (COVID-19) has badly affected our life during the year 2020. SARS-CoV-2 is the primary causative agent of the newly emerged pandemic. Natural flavonoids, Terpenoid and Thymoquinone are tested against different viral and host-cell protein targets. These natural compounds have a good history in treating Hepatitis C Virus (HCV) and Human Immunodeficiency Virus (HIV). Molecular docking combined with cytotoxicity and plaque reduction assay is used to test the nat… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Some drawbacks probably related to the extraction of these compounds from plants or the chemical synthesis difficulties did not permit further biological investigations. Recently, in-vitro study revealed that neohesperidin could inhibit infected Vero E6 cell [ 141 ].…”
Section: Resultsmentioning
confidence: 99%
“…Some drawbacks probably related to the extraction of these compounds from plants or the chemical synthesis difficulties did not permit further biological investigations. Recently, in-vitro study revealed that neohesperidin could inhibit infected Vero E6 cell [ 141 ].…”
Section: Resultsmentioning
confidence: 99%
“…The integral protective properties and relevant physicochemical functions executed by TQ in both the extra-and intracellular space have been recently compiled [17]: In short, TQ is a small hydrophobic molecule with the capacity to bind to the viral spikes, to bind to the viral envelope, to oxidize the virus, to scavenge reactive oxygen species (ROS) -after oxidation of the virus -and to enter cells and raise endosomal pH. In addition to its antiviral potential, demonstrated in vitro using human-derived SARS-CoV-2 [18], TQ presents broad antibacterial, anti-inflammatory, and immunomodulatory effects.…”
Section: Methodsmentioning
confidence: 99%
“…124 Other studies have shown that TQ might display inhibitory action against the SARS CoV2 protease, which would halt viral replication. 120 , 125–127 …”
Section: Potential Beneficial Effects Of Thymoquinone In Covid-19mentioning
confidence: 99%
“…52 Nigella sativa extract containing TQ has also, more specifically, been reported to decrease viral replication and loads in cells infected with some coronaviruses. 119 Interestingly, one in vitro study demonstrated that TQ showed significant antiviral activity against a SARSCoV-2 strain isolated from Egyptian patients, 120 possibly through blocking the entry of the virus into the cells. 121 Overall, the existing studies highlight the immense potential of TQ as an effective antiviral agent against COVID-19, a premise which is highly supported by the molecular docking studies examining TQ's effects against various virus and host cell targets, which are discussed in more detail in the following section.…”
Section: Antiviral Activitymentioning
confidence: 99%
See 1 more Smart Citation